The role of the support properties in the catalytic performance of an anchored copper(II) aza-bis(oxazoline) in mesoporous silicas and their carbon replicas - Silva, Ana Rosa
A copper(II) chiral aza-bis(oxazoline) catalyst (CuazaBox) was anchored onto ordered mesoporous silicas and their carbon replicas. The materials were characterized by elemental analysis (C, N, H, S), ICP-AES, FTIR, XPS, thermogravimetry and isotherms of N-2 adsorption at -196 degrees C. The materials were tested as heterogeneous catalysts in the reaction of cyclopropanation of styrene to check the effect of porous material type on the catalytic parameters, as well as on their reutilization. Generally, the composites were more active and enantioselective in the cyclopropanation of styrene than the corresponding homogeneous phase reaction run under similar experimental conditions. The materials pH(pzc) proved to be an important factor not only in the CuazaBox anchoring yields, but also in their catalytic performance. Less acidic surfaces (SPSi and CMK-3) yielded heterogeneous catalysts with higher styrene conversion and enantioselectivity. The materials could also be recycled with comparable enantioselectivities or generally a slight decrease in the enantioselectivity.